Quantitative measurement of nanofriction between PMMA thin films and various AFM probes. (15th January 2021) - Grzywacz, Hubert; Milczarek, Michał; Jenczyk, Piotr; Dera, Wojciech; Michałowski, Marcin; Jarząbek, Dariusz M.
Highlights: Atomic force microscope cantilever calibrated with high precision and accuracy. Influence of tip material and tip radius on the friction coefficient is shown. Coefficient of friction measured in relation with normal load and friction speed. Abstract: This study reports the quantitative, precise and accurate results of nanoscale friction measurements with the use of an Atomic Force Microscope calibrated with a precise nanoforce sensor. For this purpose, three samples of spin-coated thin Polymethylmethacrylate (PMMA) films were prepared with the following thicknesses: 235, 343, and 513 nm. Three different AFM probes were used for the friction measurements: with diamond-like carbon (DLC) tip with a small (15 nm) or big (2 µm) tip radius, and a reference silicon tip with a small (8 nm) radius. The results show that in all of the studied cases, the coefficient of friction strongly depends on the applied load, being much higher for a lower load. Furthermore, a strong relation of the friction force on the cantilever's geometry, the scanning velocity, and the film thickness was observed.